Intaosseous synovial sarcoma of the proximal femur : Case Report - Zulkarnaen, M.; Pan, K.L.; Shanmugam, P.S; Ibrahim, Z.A.; Chan, W.H (Malaysian Orthopaedic Journal, 2012)
Synovial sarcoma is primarily a soft tissue malignancy that most often affects adolescents and young adults. It very rarely presents as a primary bone tumour and has only been reported in nine other cases to date. We report a case of primary synovial sarcoma arising from the proximal femur in a 57-year-old man.